2022
DOI: 10.1002/adfm.202203894
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution of C60 Molecular Crystal Predicted by Neural Network Potential

Abstract: The preparation of fullerene and a wide range of derivatives has attracted much attention in past decades. Understanding the structural evolution starting from fullerene is critical to guide the experimental exploration but has been paid less attention yet. Using ab initio molecular dynamics or global structural search algorithm accompanied with density functional theory calculations can give a glance of the potential energy surface (PES), but suffers high cost and low efficiency. Herein, by using neural netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The unique configuration of the C 70 precursor should be responsible for the amorphous structure formed, and for its superior properties. As we know, fullerene cages collapse under pressure, accompanied with sp 2 − sp 3 bonding changes 53 , 54 . In this case, from the topological transition point of view, the presence of both hexagons and pentagons makes formation of an ordered structure unlikely 30 , but overheating could induce re-crystallization and diamond formation, as observed in our comparison experiments.…”
Section: Discussionmentioning
confidence: 97%
“…The unique configuration of the C 70 precursor should be responsible for the amorphous structure formed, and for its superior properties. As we know, fullerene cages collapse under pressure, accompanied with sp 2 − sp 3 bonding changes 53 , 54 . In this case, from the topological transition point of view, the presence of both hexagons and pentagons makes formation of an ordered structure unlikely 30 , but overheating could induce re-crystallization and diamond formation, as observed in our comparison experiments.…”
Section: Discussionmentioning
confidence: 97%
“…14,15 Starting from precursors of C 60 , the structural evolution of atomically disordered diamonds by sp 2 to sp 3 hybridization and the corresponding pressure− temperature dependence were reported through simulations. 15,16 With an adiabatic-bias MD technique, 17 Tang et al also obtained p-D with paracrystalline fraction up to 70%, 15 successfully bridging the temporal gap between the experiment and simulation. However, the temperature effect on the formation of sp 3 -rich amorphous carbons is still ambiguous, further impeding us to fundamentally understand why atomically disordered sp 3 -hybridized carbons can be formed unexpectedly and how to obtain them under suitable HPHT conditions.…”
mentioning
confidence: 96%
“…Recently, Shang et al and Tang et al coincidentally reported atomically disordered diamonds with a sp 3 concentration close to 100%. The synergistic control of high-pressure and high-temperature (HPHT) conditions in their experiments revealed that atomically disordered diamonds can be obtained only within a narrow temperature range. , Starting from precursors of C 60 , the structural evolution of atomically disordered diamonds by sp 2 to sp 3 hybridization and the corresponding pressure–temperature dependence were reported through simulations. , With an adiabatic-bias MD technique, Tang et al also obtained p-D with paracrystalline fraction up to 70%, successfully bridging the temporal gap between the experiment and simulation. However, the temperature effect on the formation of sp 3 -rich amorphous carbons is still ambiguous, further impeding us to fundamentally understand why atomically disordered sp 3 -hybridized carbons can be formed unexpectedly and how to obtain them under suitable HPHT conditions.…”
mentioning
confidence: 99%
“…In recent reporting on Nature (https://www.nature.com/ articles/s41586-022-05532-0), Yanwu Zhu, Rodney S. Ruoff, and their colleagues have synthesized a crystalline porous carbon constructed with covalent connected broken C 60 cages through a facile electron injecting approach that can be easily scaled up [16]. The C 60 molecule is an electron-acceptor, and injecting electrons into C 60 molecules can promote their reactivity.…”
mentioning
confidence: 99%